Analisis Komunikasi Keterbukaan Diri Melalui Akun Kedua Instagram Pada Mahasiswa Ilmu Komunikasi Angkatan 2021 Universitas Mulawarman - Damayanti, Afni Dwi; Sugandi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Science students in the 2021 batch of Mulawarman University on the second account of Instagram. This research uses a qualitative approach with descriptive methods. With a research focus using the theory of self-disclosure (Johari Window) which has four concepts, namely the concepts of open, blind, hidden, and unknown. This research consists of five informants. By using the in-depth interview method, this research uses a sampling technique, namely purposive sampling to determine informants to match the research criteria. Data analysis techniques were carried out by reducing data, presenting data, and drawing conclusions developed by Miles and Huberman. The results of this study indicate that every 2021 Communication Science student of Mulawarman University makes Instagram a medium for self-disclosure, especially Instagram's second account, which can maintain all forms of information exchange and good friendships. The largest area found in Communication Science students in the Class of 2021 in using a second account is the Open Self area and there are also several reasons for doing self-disclosure in Communication Science students in the Class of 2021, namely to feel more free to express, feel more comfortable and enjoy, have control over followers who see posts, and avoid negative comments or other people's talk.